Från gles skog och brokiga ungskogar till homogen produktionsskog - Holmgren, Ola (2004)
The forest in the northern part of Sweden has changed dramatically during the last centuries. The forest has gone through a large-scale transformation, from it being only used locally for domestic purposes to becoming very important raw material for Sweden in the industrial age. The strategy by foresters during the second half of the 20th century has been to create pure production forests for commercial forestry. This has mainly succeeded and we have today homogenous production forests that give a high profit to the owners. The aim of the study is to compare the state of the forest in the former state forest Hällforsmarken in the years 1925 and 2000 and to interpret the changes which has taken place. The study is based on historical and modern maps and forest inventories, literature and conversations with persons who has connection to the studied area. The study mainly shows that the standing volume in the forest has increased substantially within the area over the last 75 years. The age-structure of the forest has also changed substantially, from old and uneven-aged forest stands to young and even-aged forest stands. The species composition has shifted towards and increase of Scots pine. Pinus contorta has been introduced by afforestation in the area of the study. The reason that the forest in the area of the study has changed so radically is due to the fact that it first was used by a local sawmill (Ytterstfors) from 1886. At this point the exploitation of the old-growth forest began. This effected the state of the forest substantially. By the time the state (Domänverket) took over the forest it was in a bad shape when it comes to timber-production. The state of the forest in the park was described at the time to mainly consist of old sparse mixed coniferous forest with low standing volume. At the construction of forest inventory in 1925, the primary goal to fell all remaining large trees in the young forests that was in the area. This was the first measure that made the multistoried forests to disappear. The next goal in the forest inventory plan was to improve the skewed age-structure mainly in Nymyrheden kronopark. These two goals were the starting point for the transformation from multistoried forests to homogenous production forests which today dominate the area of the study.